Black food : stories, art and recipes from across the African diaspora - Terry, Bryant, 1974- (4 Color Books, an imprint of Ten Speed Press, 2021)
"A beautiful, rich, and groundbreaking book exploring Black foodways within America and around the world, curated by food activist and author of Vegetable Kingdom Bryant Terry"--